Effect of Trataka (Yogic Visual Concentration) on the Performance in the Corsi-Block Tapping Task: A Repeated Measures Study - Swathi, P. S.; Bhat, Raghavendra; Saoji, Apar Avinash (Frontiers in Psychology, 2021)
Background and Objective: Attention and memory are essential aspects of cognitive health. Yogasanas, pranayama and meditation have shown to improve cognitive functions. There has been no assessment of Trataka (yogic visual concentration) on working or spatial memory. The present study was planned to assess the immediate effects of Trataka and eye exercise sessions on the Corsi block tapping task (CBTT). Methods: Forty-one healthy volunteers of both genders with age 23.21 ±2.81 yrs were recruited. Each participant was assessed in three sessions conducted on three separate days at the same time of the day. The three sessions were baseline, Trataka and eye exercise. Repeated measure analysis of variance with Holm's adjustment was performed to check the difference between the sessions. Results: Significant within-subjects effects were observed for forward Corsi span & forward total score (p<0.001), backward Corsi span (p<0.05) and the backward total score (p<0.05). Post-hoc analyses revealed Trataka session to be better than eye exercises and baseline. The eye exercise session did not show any significant changes in the CBTT. Conclusions: The result suggests that Trataka session improves working memory, spatial memory, and spatial attention.